EKSISTENSI POS BANTUAN HUKUM (POSBAKUM) DALAM MEMBERIKAN LAYANAN HUKUM PADA MASYARAKAT MISKIN DI KOTA PALOPO - Hardianto Hardianto (Al-Amwal : Journal of Islamic Economic Law, 2020)
The problem in this study is to find out the legal aid posts (posbakum) in the district courts and religious courts and the existence of posbakum in providing legal aid services to the poor in Palopo City. This research is a descriptive normative research with empirical and normative approaches. The results showed that the Posbakum in the Palopo Religious Court was formed in February 2019, and has handled 104 cases, while the Palopo District Court began to form since the issuance of the Supreme Court Regulation of the Republic of Indonesia Number 1 of 2014 regarding the establishment of Legal Aid Posts (POSBAKUM) in every court throughout Indonesia and has handled thousands of cases. In their service, both the Palopo Religious Court and the Palopo District Court do not distinguish between the poor and the rich, all of them can request/request legal assistance from Posbakum by completing the requirements. Based on the researcher's questionnaire and direct interviews with respondents, the poor people who do not know about posbakum because they have never been involved in legal problems in court, while those who know about posbakum are poor people who have been involved in legal problems in court.